1991
DOI: 10.1111/j.2042-7158.1991.tb03189.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Amphotericin B Lipid Complex in Laboratory Animals

Abstract: Amphotericin B lipid complex (ABLC), under development for the treatment of serious fungal disease, is not a true liposome but a complex of amphotericin B, dimyristoyl phosphatidylcholine and dimyristoyl phosphatidylglycerol with a particle size range of 1.6-6.0 microns. Tissue distribution of ABLC was determined in mice and rats after i.v. or i.p. administration. ABLC resembles typical liposomal preparations with amphotericin B concentrating in the reticuloendothelial system. After a single i.v. treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…CAS pharmacokinetics are very similar across species, and our choice of doses ranged from 1 to 10 mg of CAS per kilogram of body weight; others have shown that a dose of 5 mg/kg results in blood levels similar to those in patients (greater than 1 g/ml at 24 h postdose) (14,19,21,37); similar serum concentrations of MICA have been reported (15,20,30,31). Although the amphotericin B preparations used in our study have slightly different pharmacokinetics in humans (2-4, 23), the dosages used with the mice in our study result in serum concentrations equivalent to those in humans (32,34,36,48). In addition to these considerations, the dose ranges chosen have been reported to be efficacious in various animal models of aspergillosis (1,13,25,26,30,33,(39)(40)(41)51).…”
Section: Discussionsupporting
confidence: 50%
“…CAS pharmacokinetics are very similar across species, and our choice of doses ranged from 1 to 10 mg of CAS per kilogram of body weight; others have shown that a dose of 5 mg/kg results in blood levels similar to those in patients (greater than 1 g/ml at 24 h postdose) (14,19,21,37); similar serum concentrations of MICA have been reported (15,20,30,31). Although the amphotericin B preparations used in our study have slightly different pharmacokinetics in humans (2-4, 23), the dosages used with the mice in our study result in serum concentrations equivalent to those in humans (32,34,36,48). In addition to these considerations, the dose ranges chosen have been reported to be efficacious in various animal models of aspergillosis (1,13,25,26,30,33,(39)(40)(41)51).…”
Section: Discussionsupporting
confidence: 50%
“…In single-and multidose distribution studies of rodents that used equimolar dosages of 1 mg/kg of the parent drug, concentrations in whole-lung homogenates achieved with ABCD and LAMB were lower and those achieved with ABLC were similar or slightly higher than those achieved with DAMB as the reference agent. After multiple dosing of 5-fold (ABCD and LAMB)-to 10-fold (ABLC)-higher dosages, drug accumulation in the lungs clearly exceeded that achieved by 1 mg/kg of DAMB (20,21,28). These differences in lung distribution appear to correspond to the results of comparative pulmonary infection models, where the lipid formulations required at least fivefold-higher dosages to produce a reduction of the residual fungal burden in lung tissue equivalent or superior to that produced by standard dosages of DAMB (1,8,10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AmB lipid complex concentrates in the liver, spleen and lungs, and to a lesser extent, in bone marrow. 105,113 The Abelcet 1 exposure in the lung exceeds that of Ambisome 1 . 114,115 Abelcet 1 acts as a depot formulation that rapidly distributes AmB to tissue stores, from which it releases AmB slowly.…”
Section: Abelcetmentioning
confidence: 99%